(untitled) (Biological Sciences - PJSIR, 2008)
The human fetus exists in an environment in which there is an apparent over-abundance of prostaglandins (PGs). Neonates are also believed to contain high concentrations of PGs. Since both fetus and the neonate have a significant potential for prostaglandin catabolism, it may be inferred that some benefits accrue from a prostaglandin rich environment and that prostaglandins (PGs) are serving important roles in both intrauterine and early extrauterine life. Prostaglandins are formed from non-esterified arachidonic acid (AA) by the action of cyclooxygenase (COX). AA is also metabolized by way of lipoxygenase enzyme pathway. Products of this pathway are known to modulate prostaglandin biosynthesis. Little information is available concerning these pathways in fetal and neonatal tissues. In this review article, the results of studies designed to evaluate AA metabolism in the fetus and the neonate are described. In addition, AA metabolism in uterine and intrauterine tissues is also considered, since the products of such metabolism are important for normal fetal growth and development.